Information from social networking sites: Context collapse and ambiguity in the hiring process. (15th September 2017) - Pike, Jacqueline C.; Bateman, Patrick J.; Butler, Brian S.
Abstract: Forming impressions of job candidates is a challenging process, one characterized by ambiguity brought about by the uncertainty associated with making decisions and judgments. To reduce ambiguity, hiring professionals have established policies and procedures to facilitate the sourcing and use of information about a candidate. However, recently, a public source of information is increasingly being used—information from social networking sites (SNSs). While conventional wisdom says more information is better and can help make decisions less ambiguous, this relationship may not be as straightforward as expected when facing assessments of candidates. This paper examines two such aspects, information‐task quality and context collapse, and their collective impact on ambiguity when making an assessment of a job candidate. Using data from an online survey‐based experiment, the findings suggest information from SNSs can be useful, yet can create ambiguity for decision makers because of context collapse made possible by SNS technologies.